A vulnerabilidade nas relações jurídico-consumeristas: uma análise da desvantagem linguística perante a lei - Andrade, Tadeu Luciano Siqueira (Language and Law / Linguagem e Direito, 2019)
In legal-consumer relations, there will always be someone in a state of vulnerability, at a disadvantage vis-a-vis the supplier, who has the technical knowledge of the production and supply of the product/service and who can therefore get what he wants, because of the consumer lack of preparedness. This explains the consumer’s vulnerability. Just being a consumer is to be vulnerable (Nunes, 2012). There are several types of vulnerability: technical, legal (or scientific), phatic (socioeconomic) and informational. For this article, what is of interest is linguistic vulnerability because in the case analyzed the legislator recognizes that the consumer is ignorant of the areas of legal accounting, economics, mathematics and others, given their linguistic peculiarities. We describe linguistic vulnerability in legal-consumer relations, starting from semantics and pragmatics, given the function and meaning of these areas in legal discourse. Adopting the theoretical-methodological assumptions of bibliographical research and based on consumer legislation and on the work legal theorists and linguists, we analyze a specific case dealt with in the Vara das Relações de Consumo da Comarca de Conceição do Coité (BA), which exemplifies a typical case of linguistic disadvantage before the law. This paper presents some perspectives on the language of the Law, exemplifying the relation between Law and Language, with an emphasis on linguistic vulnerability.